2017
DOI: 10.3844/ajeassp.2017.679.684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distance of the Submerged Vanes from the Outer Bank on Sediment Movement within 180° Bend

Abstract: A small aspect ratio of submerged vanes when used near the outer bank at the angle of attack between 10° to 20° and at the initial height above the bed between 20-40% of flow depth is considered one of the most successful river training structures. Vanes when located within the bends of river, produces helical swirls at inverse action with the centrifugally secondary current action. Accordingly, its existence leads to mitigate the influence of the secondary current, thus reducing the outer bank erosion. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Among the different design parameters of submerged vanes, the angle of attack of the vane with the ow is an important parameter, and it has been the subject of various investigations. For example, many researchers studied the effect of vane angle of attack to control and reduce scour [6, 10,13,19,24,25,30,31,32,34,38,40,43,45,46].…”
Section: Application Of Submerged Vanesmentioning
confidence: 99%
“…Among the different design parameters of submerged vanes, the angle of attack of the vane with the ow is an important parameter, and it has been the subject of various investigations. For example, many researchers studied the effect of vane angle of attack to control and reduce scour [6, 10,13,19,24,25,30,31,32,34,38,40,43,45,46].…”
Section: Application Of Submerged Vanesmentioning
confidence: 99%
“…The results of their study indicated a desirable relationship between experimental and numerical results. Maatooq and Adhab (2017) analyzed the effect of the distance of the submerged vanes from the outer bank of the channel on sediment reach along the channel. To this aim, they installed the submerged vanes at different distances from the outer bank in a 180 degree bended channel.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the riverbed degrades in one portion of the channel cross-section and degrades in another. Generally, submerged vanes are used for river channel stabilization, bank protection, shoaling amelioration, control and reduction of scour, and sedimentation at diversions and water intakes [13][14][15][16][17][18][19][20] . Additionally, submerged vanes can be used to increase the turbulence of flows upstream of the bottom outlets of reservoirs and, finally, to increase the amount of evacuated sediment.…”
mentioning
confidence: 99%